The Effect of Customer Value on Behavioral Intentions in Tourism Industry - Wahyuningsih, Wahyuningsih (International Research Journal of Business Studies, 2012)
Customer value is a recent line of research that is attracting the attention of the marketers. The objective of this study is to investigate tourists’ perceived value and its effect on future behavioral intentions of tourists to revisit. Data have been collected through questionnaires which were supported by in-depth interviews with tourists visiting Togean Islands, one of the most popular tourism destinations in Indonesia. The proposed research model of has been tested using Stuctural Equation Modeling. Results of this study that tourists who perceive higher levels of value will have stronger intentions to revisit the tourism destination and will recommend it to other people. Three main aspects which are needed to be improved to increase the number of tourists to visit Togean Islands are communications, transportations, and cleanliness. This study also provides managerial implications, conclusion, and future research directions.